An environmental equalizer for underwater acoustic communications Tested at Hydralab III - Silva, A. (2012)
It is known that small changes in source and receiver locations can cause significant changes in underwater acoustic channel impulse responses. At HYDRALAB III an underwater acoustic experiment was conducted to show that a source depth-shift causes a frequency-shift in the channel impulse response and that such behavior can be used to implement an environmental-based equalizer for underwater communications that compensates for the performance loss due to the source depth-shift.